Pengaruh Intellectual Quotient (IQ), Emotional Quotient (EQ) Dan Spiritual Quotient (SQ) Terhadap Kinerja Karyawan - Salman Al Halili; Hadi Sunaryo; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study was conducted to determine the effect of Intellectual Quotient (IQ), Emotional Quotient (EQ) and Spiritual Quotient (SQ) on the Performance of Employees in the Office of the City of Malang City of East Java. Which is located at Jl. Bingkil NO.1 Ciptomulyo, Sukun District, Malang City. The method used is explanatory research is a research method that aims to explain the position of the variables studied as well as the influence between one variable with another variable, and the source of the data used is primary data that is by distributing linkie cyclists to the employees of the Malang City Hygiene Office. The sample calculation in this study uses the Slovin formula which produces 84 respondents. The results of this study are the Intellectual Quotient (IQ), Emotional Quotient (EQ) and Spiritual Quotient (SQ) variables simultaneously and partially on Employee Performance. Keywords: Effect of Intellectual Quotient (IQ), Emotional Quotient (EQ), Spiritual Quotient (SQ) and Employee Performance